Growth and Production of Sweet Corn (Zea mays var. Saccharata Strut.) at Various Doses of NPK 16-16-16 Fertilizer - Astryani Rosyad; Erik Mulyana; Hafith Furqoni; Suwarto Suwarto; Adrian Khairullah; Annas Sofian (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Sweet corn is a high-value horticultural crop with steadily increasing demand for both fresh consumption and use as a raw material in the food industry. This study aims to evaluate the effectiveness of NPK 16-16-16 fertilizer on the growth and yield of sweet corn. The research was conducted at Sindangbarang Experimental Field, Faculty of Agriculture, IPB University from July to October 2025. This experiment used a Randomized Complete Block Design (RCBD) with a single factor, namely the dose of fertilizer application. Treatments were using fertilizer dosages of 0, 50, 0,75, 1,00, and 1,50 NPK 16-16-16, with a control treatment for comparison. During the vegetative phase, sweet corn exhibited similar growth responses across all fertilization levels relative to the control. However, all fertilizer doses significantly improved stover weight, cob weight with and without husk, cob length, cob diameter, yield per plot, and overall productivity compared to the control. The application of NPK 16-16-16 fertilizer at the recommended (1.0) rate achieved the highest relative agronomic effectiveness (103.11%), corresponding to a 1.03-fold yield increase over the control and outperforming the comparison treatment. Application of NPK 16-16-16 at the 1.0 recommended dose is suggested as the most efficient fertilization strategy for sweet corn production, as it maximizes yield and productivity without unnecessary increases in fertilizer input.